DEEP LEARNING FROM SCRATCH BUILDING WITH PYTHON FROM FIRST PRINCIPLES - WEIDMAN SETH; WEIDMAN SETH (NAVI MUMBAI O'REILLY SPD PVT.LTD, 2024)
DEEP LEARNING FROM SCRATCH BUILDING WITH PYTHON FROM FIRST PRINCIPLES
PYTHON PRINCIPLES
COMPUTERS
DATA SCIENCE AND ATRIFICIAL INTELLIGENCE
Keywords: WEIDMAN SETH; DEEP LEARNING FROM SCRATCH; PYTHON